BEHAVIOR OF PERSONAL PROTECTIVE EQUIPMENT (PPE) USE IN THE IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY (OSH) - Dadan Herman Darusman; Titin Ruliana; Sayid Irwan (IJEBD (International Journal of Entrepreneurship and Business Development))
Purpose:  The purpose of this research is to analyze the behavior of using Personal Protective Equipment (PPE) in the implementation of Occupational Health and Safety (OHS). The behavior of using Personal Protective Equipment consists of government regulations, company policies, and employee compliance. Design/methodology/approach:   This research uses a descriptive quantitative approach. The data collection techniques include questionnaires and documentation. The data analysis tool used is regression and path analysis with SPSS application.